POTRET PEREMPUAN REMAJA URBAN DALAM NOVEL TEENLIT LOVE ME MARRY ME KARYA ESTHER PRISCILLA - Putri, Meza Junita; Hayati, Yenni (Universitas Negeri Padang, 2019)
The study aims to describe the portraits of urban teenage women in the teenlit Love Me Marry Me by Esther Priscilla, which includes: personality pleasures, recreational prestige, and adolescent female delinquency. This type of research is qualitative research using descriptive methods. Data collection is conducted through: (1) reading and understanding the novel Love Me Marry Me by Esther Priscilla to gain an understanding of the novel; (2) Set a character in Love Me Marry Me by Esther Priscilla using the format; (3) Identifying data in accordance with the research issues; and (4) data input. Based on the results of the data analysis, obtained: (1) Personality pleasures on the urban teenage female figures in the teenlit Love Me Marry Me by Esther Priscilla include picnics and dancing; (2) The recreational prestige of the urban teen women depicted in Teenlit Love Me Marry Me by Esther Priscilla in general has fast food restaurants, owning a villa, having private ventures such as car showrooms, boutiques, and bridal; (3) in Teenlit Love Me Marry Me by Esther Priscilla There is no data on the delinquency of urban adolescents, as the novel Love Me Marry Me by Esther Priscilla is more about the struggle and sacrifice of a willing woman was married to a man who initially did not like her to happy her father.Â Keywords: women, sacrifice, marriageÂ The study aims to describe the portraits of urban teenage women in the teenlit Love Me Marry Me by Esther Priscilla, which includes: personality pleasures, recreational prestige, and adolescent female delinquency. This type of research is qualitative research using descriptive methods. Data collection is conducted through: (1) reading and understanding the novel Love Me Marry Me by Esther Priscilla to gain an understanding of the novel; (2) Set a character in Love Me Marry Me by Esther Priscilla using the format; (3) Identifying data in accordance with the research issues; and (4) data input. Based on the results of the data analysis, obtained: (1) Personality pleasures on the urban teenage female figures in the teenlit Love Me Marry Me by Esther Priscilla include picnics and dancing; (2) The recreational prestige of the urban teen women depicted in Teenlit Love Me Marry Me by Esther Priscilla in general has fast food restaurants, owning a villa, having private ventures such as car showrooms, boutiques, and bridal; (3) in Teenlit Love Me Marry Me by Esther Priscilla There is no data on the delinquency of urban adolescents, as the novel Love Me Marry Me by Esther Priscilla is more about the struggle and sacrifice of a willing woman was married to a man who initially did not like her to happy her father.Â Keywords: women, sacrifice, marriage